Биология черного медляка (Oodescelis polita Sturm) в лесостепной и степной зонах Европейской части СССР - Кабанов, В.А. (Вестник зоологии, 1978)
The life cycle of Oodescelis polita Sturm is described within the limits of the mentioned region and certain stages of its development are considered in detail. An approximate scale is suggested to determine the larva age. Generation of O. polita is biennial. The sum of efficient temperatures (above 12°C) necessary for development from the egg to imago within one generation is 2784°.